Análise elasto-plástica da construção de aterros - Iturri, Edwin Alvaro Zuleta (1991)
This work presents a comparative study of the stress, strain and displacement conditions of Formoso "A" canal, considering the construction sequence. The state of stresses, strains and displacements is obtained using the Finite Element Method with both elastic and elasto-plastic analysis. The program uses both quadratic isoparametric quadrilateral elements and triangular elements with six nodes. The stresses and strains are computed at the integration points of each element. In the elastic nonlinear analysis the formula proposed by Duncan and Chang (1970) is used and for the Poisson's ratio the exponential formulation published by Lade (1972) is applied. In the elasto-plastic analysis the formula proposed by Drucker and Prager (1952) and Drucker (1953) and the new formulation of Kim and Lade (1988), wich uses only one plastic surface, are employed. The technique used for the nonlinear analysis is incremental, taking into account the modification of the middle point of Runge Kutta. For the elasto-plastic analysis an incremental-iterative technique combined with the initial stress method is applied, including convergence acceleration using the Line Search Method for the Drucker and Prager model. ln the initial stress technique, the algorithm proposed by Zienkiewicz et al. (1969) with changes suggested by Nayak and Zienkiewicz (1972) is employed, while the algorithm proposed by Crisfield (1983) is used to accelerate the convergence.